-y+4+3y=

Simple and best practice solution for -y+4+3y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -y+4+3y= equation:


Simplifying
-1y + 4 + 3y = 0

Reorder the terms:
4 + -1y + 3y = 0

Combine like terms: -1y + 3y = 2y
4 + 2y = 0

Solving
4 + 2y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 2y = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 2y = 0 + -4
2y = 0 + -4

Combine like terms: 0 + -4 = -4
2y = -4

Divide each side by '2'.
y = -2

Simplifying
y = -2

See similar equations:

| 3a=8m+18 | | 4n+8-2n=0 | | 3(k-2)=-5 | | 9.5=1.4d-3.1 | | 4n+-2n=0 | | x-12/10=x-6/7 | | -8(2c+20)=2(-6c-10)+6c | | x^2+13x+15=2x+5 | | 5+5lnx=3 | | y=16+-1x^2 | | 81x^2-7=57 | | (-7)(2j-27)=49j | | -20-6k=-8(6k-16)+20 | | (p^2)-(2p)+6=2 | | x^2+30x+100=70x-x^2 | | 5(i+4)=15i | | 3(-6m+10)=2(-10m+17) | | z+8z+12=15 | | (-1/4t^3u^9)^4 | | 5(3y+10)-4y=17 | | 9z+12=15 | | 6(-5+11y)=3(6y+6) | | 3(4-3h)=-6 | | 3x+8-7(x+1)=-(6x-6) | | 4f-17=-3-3f | | 6(-3s-20)=6-11s | | 15y-4x=-33 | | 3-4e=27-e | | -9(-d+16)=-3+6(8d+9) | | (4xy)(4xy)=equation | | 48x^2+30x+10=0 | | (b+1)(b+1)= |

Equations solver categories